Assessing the Functioning of Land Rental Markets in Ethiopia - Deininger, Klaus; Ali, Daniel Ayalew; Alemu, Tekie (World Bank, Washington, DC, 2012)
Although a large theoretical literature discusses the possible inefficiency of sharecropping contracts, the empirical evidence on this phenomenon has been ambiguous at best. Household-level fixed-effect estimates from about 8,500 plots operated by households that own and sharecrop land in the Ethiopian highlands provide support for the hypothesis of Marshallian inefficiency. At the same time, a factor adjustment model suggests that the extent to which rental markets allow households to attain their desired operational holding size is extremely limited. Our analysis points towards factor market imperfections (no rental for oxen), lack of alternative employment opportunities, and tenure insecurity as possible reasons underlying such behavior, suggesting that, rather than worrying almost exclusively about Marshallian inefficiency, it is equally warranted to give due attention to the policy framework within which land rental markets operate.